Analysis of Financial Technology (Fintech) on Financial Literacy and Inclusion of Students in South Jakarta - Muhammad Nur Fahruqi; Winda Amelia (Majapahit Journal of Islamic Finance and Management, 2025)
This study was motivated by the rapid adoption of Financial Technology (FinTech) among students, which has the potential to strengthen financial literacy and inclusion, but still leaves a gap between access and understanding of safe and responsible use. The objectives are to analyse the effect of FinTech usage on digital financial literacy and financial inclusion, assess the effect of literacy on inclusion, and examine the mediating role of literacy in the relationship between FinTech usage and inclusion. The method used is a cross-sectional quantitative survey of 150 students in South Jakarta using a Likert scale questionnaire, processed through descriptive statistics and SEM-PLS to test the structural model. The results show that: (1) FinTech usage has a positive and significant effect on digital financial literacy; (2) FinTech usage has a positive and significant effect on financial inclusion; (3) digital financial literacy has a positive and significant effect on inclusion; and (4) digital financial literacy significantly mediates the effect of FinTech usage on inclusion. These findings confirm the dual role of FinTech as a gateway to formal services and a vehicle for practical learning, with literacy as the key to safe, responsible, and sustainable financial participation among students. The implication is that the integration of digital payment literacy into the campus ecosystem and collaboration between universities, regulators, and industry need to be strengthened to improve the quality of financial inclusion.